2011
DOI: 10.1242/dev.068080
|View full text |Cite
|
Sign up to set email alerts
|

Rapid BAC selection fortol2-mediated transgenesis in zebrafish

Abstract: SUMMARYThe generation of zebrafish transgenic lines that express specific fluorophores in a cell-or tissue-specific manner is an important technique that takes full advantage of the optical clarity of the embryo. Identifying promoter fragments that faithfully recapitulate endogenous expression patterns and levels is often difficult and using large genomic DNA fragments, such as bacterial artificial chromosomes (BACs), makes the process of transgenesis less reliable. Here we provide a detailed protocol that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
170
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(174 citation statements)
references
References 29 publications
4
170
0
Order By: Relevance
“…However, recent reports have shown that much larger transgenes can be transposed. Tol2 vectors have been used to mobilize a bacterial artificial chromosomes (BAC) into the genome of early vertebrate embryos (42,43). Similarly, a piggyBac vector has been used to integrate sequences of up to 100 kb in length (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent reports have shown that much larger transgenes can be transposed. Tol2 vectors have been used to mobilize a bacterial artificial chromosomes (BAC) into the genome of early vertebrate embryos (42,43). Similarly, a piggyBac vector has been used to integrate sequences of up to 100 kb in length (44).…”
Section: Discussionmentioning
confidence: 99%
“…BAC clone (number 74B2) from the DanioKey zebrafish BAC library containing the six2a and six3a genes was purchased from Source BioScience. Recombiant BACs were generated as previously described (36,37). For further details, see SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate further analysis of abcc6a expression, a reporter construct was prepared by introducing the GAL4 element into the start codon of the abcc6a gene via BAC recombineering (Bussmann and Schulte-Merker, 2011). The mosaic expression of Tg(abcc6a: gal4;uas:gfp) at 7 dpf revealed GFP in the notochord and in cells near the operculum and cleithrum ( Fig.…”
Section: Introductionmentioning
confidence: 99%